Surgical treatment of anaemia – is it possible? Large hiatal hernia as a cause of severe iron-deficiency anaemia - B. Feret, Wiktoria; Nalewajska, Magdalena; Ciechanowski, Kazimierz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2022)
A 65-year-old woman was referred to the Department of Internal Medicine due to severe microcytic anaemia. She complained of progressive fatigue for the past 4 months. Clinical examination revealed pallor and tenderness to palpation in the upper abdomen; per rectum examination did not reveal any signs of active gastrointestinal bleeding. Laboratory tests demonstrated substantial iron-deficiency anaemia with haemoglobin and iron levels of 6.8 g/dl (norm: 12.3–16 g/dl) and 12 µg/dl (norm: 33–193 µg/dl), respectively, and MCV 66.5 fl (norm: 81–101 fl). Other serum parameters, including the concentration of gastrointestinal tumour markers and coagulation panel, remained within the reference range. Her medical history was relevant for upper-gastrointestinal bleeding, oesophagitis grade B in LA classification, Helicobacter pylori infection, and hypertension. She had previously been repeatedly hospitalized for symptomatic microcytic anaemia with the need for blood transfusions and IV iron infusions because she did not tolerate oral iron supplementation.